2022
DOI: 10.36740/wlek202202111
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Type 1 in Adolescents: Impact of Vitamin D Status

Abstract: The aim: To evaluate the effect of vitamin D deficiency or insufficiency on the compensation of the disease in adolescents with diabetes mellitus type 1. Materials and methods: 124 patients were examined, among them: 33 from the control group, 91 adolescents with type 1 diabetes mellitus. All patients were between 10-18 years old and were residents of the Podillya region of Ukraine. Results: According to the results of the study Vitamin D levels in adolescents with type 1 diabetes mellitus are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…The main characteristics of the 45 included studies are shown in Table 1. In accordance with the recommended NOS and AHRQ criteria, only studies of acceptable quality were included in the present meta-analysis; eight studies received 9 stars [51,53,[56][57][58]62,63,66], ten studies received 8 stars [43,[48][49][50]52,54,55,[59][60][61], ve studies received 7 stars [42,[44][45][46][47] and one study received 6 stars [41]. When using the quality assessment criteria from the AHRQ, three studies received a score of 11 [24,29,65], ten received a score of 10 [22,25,28,29,31,33,34,36,39,40], three received a score of 9 [23,32,35], one received a score of 8 [27], one received a score of 7 [37] and two received a score of 5 [26,38], the quality assessment are shown in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 45 included studies are shown in Table 1. In accordance with the recommended NOS and AHRQ criteria, only studies of acceptable quality were included in the present meta-analysis; eight studies received 9 stars [51,53,[56][57][58]62,63,66], ten studies received 8 stars [43,[48][49][50]52,54,55,[59][60][61], ve studies received 7 stars [42,[44][45][46][47] and one study received 6 stars [41]. When using the quality assessment criteria from the AHRQ, three studies received a score of 11 [24,29,65], ten received a score of 10 [22,25,28,29,31,33,34,36,39,40], three received a score of 9 [23,32,35], one received a score of 8 [27], one received a score of 7 [37] and two received a score of 5 [26,38], the quality assessment are shown in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“…Дані щодо забезпеченості вітаміном D серед дитячого населення України на сьогоднішній день є недостатньо вивченими. Однак, відомо, що ступінь забезпеченості вітаміном D серед підлітків, які хворіють на ЦД 1 типу є незадовільною [4].…”
Section: вступunclassified
“…Vitamin D wirkt immunmodulatorisch durch den Vitamin-D-Rezeptor, der auf Pankreas-und Immunzellen vorhanden ist [18]. Es ist ebenfalls gut dokumentiert, dass Kinder und Jugendliche mit einem Typ-1-Diabetes häufiger unter einem Vitamin-D 3 -Mangel leiden [19,20] -und dass sich eine entsprechende Supplementation positiv auswirken kann [21].…”
unclassified